Hardware, Software, Peopleware, Subjectivity - Grémy, François (Methods of Information in Medicine, 2005)
Objective: This paper develops the closing address the author was asked to deliver at the MEDINFO 2004 Congress in San Francisco.Method: Starting from three working conferences, dealing with evaluation of health information systems, where he was involved, the author describes the evolution of his personal ideas.Results and Conclusions: First he proposes the main distinction between systems where the user(s) remain(s) external from the running program, from the ones where the user(s) interacting with the program become(s) the main component of the system.In the first case, the methods of evaluation are the conventional methods used in Medical Technology Assessment. In the second case, the whole knowledge in anthropology (considered in its broadest meaning), may contribute strongly to evaluation.It becomes clear that the subjectivity of the user(s), how he (or they) react(s) with the computing machinery, is a main key to the success or failure of the whole system.As the eradication of subjectivity is often considered, since the beginning of “modern times”, as a condition for progress, the author claims that such a temptation is deleterious for our civilization threatened by a comeback of barbarity, and is scientifically wrong.For that demonstration, he calls on both philosophical concepts (from Aristotle to E. Husserl, M. Henry and J. Searle), and the most recent advances of neurosciences.
Keywords: Medical information system; evaluation; subjectivity; modernity